Impact of resuscitative endovascular balloon occlusion of the aorta on gastrointestinal function with a matched cohort study - Shokei Matsumoto; Tomohiro Funabiki; Makoto Aoki; Masayuki Shimizu (Trauma Surgery & Acute Care Open)
Background Resuscitative endovascular balloon occlusion of the aorta (REBOA) can temporarily control arterial hemorrhage in torso trauma; however, the abdominal visceral blood flow is also blocked by REBOA. The aim of this study was to evaluate the influence of REBOA on gastrointestinal function.Methods A retrospective review identified all trauma patients admitted to our trauma center between 2008 and 2019. We used propensity score matching analysis to compare the gastrointestinal function between subjects who underwent REBOA and those who did not. Data on demographics, feeding intolerance (FI), time to feeding goal achievement, and complications were retrieved.Results During the study period, 55 patients underwent REBOA. A total of 1694 patients met the inclusion criteria, 27 of whom were a subset of those who underwent REBOA. After 1:1 propensity score matching, the REBOA and no-REBOA groups were assigned 22 patients each. Patients in the REBOA group had a significantly higher incidence of FI (77% vs. 27%; OR, 9.1; 95% CI, 2.31 to 35.7; p=0.002) and longer time to feeding goal achievement (8 vs. 6 days, p=0.022) than patients in the no-REBOA group. Patients in the REBOA group also showed significantly prolonged durations of ventilator use (8 vs. 4 days, p=0.023). Furthermore, there was no difference in the mortality rate between the groups (9% vs. 9%, p=1.000).Conclusions REBOA was associated with gastrointestinal dysfunction. Our study findings can be useful in providing guidance on managing nutrition in trauma patients who undergo REBOA.Level of evidence Level IVStudy type Care management